Neural Circuits Underlying Behavioral Flexibility: Insights From Drosophila - Devineni, Anita V.; Scaplen, Kristin M. (Frontiers in Behavioral Neuroscience, 2022)
Behavioral flexibility is critical to survival. Animals must adapt their behavioral responses based on changes in environmental context, internal state, or experience. Studies in Drosophila melanogaster have provided insight into the neural circuit mechanisms underlying behavioral flexibility. Here we discuss how Drosophila behavior is modulated by internal and behavioral state, environmental context, and learning. We describe general principles of neural circuit organization and modulation that underlie behavioral flexibility, principles that are likely to extend to other species.